Impacts of Pretreatment Techniques on the Quality of Tuber Flours - Abebe Desalegn Melese; Ebisa Olika Keyata (The Scientific World Journal)
Besides dietary sources of energy, roots and tuber crops can also serve as functional foods and nutraceutical ingredients to be explored in disease risk reduction and wellness. However, they are easily spoiled because of their high moisture contents and enzymatic reactions. Therefore, this review aimed at gathering information on the effects of various pretreatment methods on the quality of tuber crops before converting them into flour. Studies reported by different scholars showed that there were significant differences in physicochemical and functional properties between untreated tuber and the treated tuber samples. The review also highlighted that the chemical treatment methods, particularly sulfite treatment, could increase the lightness value of the flour. In addition, blanching could induce a decrease in protein, ash, and fat. Despite this, blanching pretreatment techniques increased moisture and carbohydrate content. Chemical treatment increases the ash content, which might be responsible for chemical diffusion into the sample. The reviewed results showed that the application of different pretreatments on tuber crops significantly improves many quality characteristics such as color, fiber content, carbohydrate, and the functional properties used for value addition during food product development in the industry. Therefore, application of pretreatment methods particularly chemical treatments could enhance nutritional value, and functional and physical properties of tuber flours.